2006
DOI: 10.1002/hyp.5963
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of remotely sensed floodplain saturation and its use in runoff predictions

Abstract: Abstract:Principal components analysis (PCA) is applied to a time series of European Remote Sensing (ERS) synthetic aperture radar (SAR) scenes of the Alzette River floodplain (Grand-Duchy of Luxembourg). These images cover markedly different hydrological conditions during several winter seasons in order to enable the examination of the decrease of the radar backscattering signal during drying-up phases following important flood events. At the floodplain scale, with homogeneous land use and constant topography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, these models are inaccurate when applied over wide regions and they aim at evaluating soil loss quantitatively, neglecting both the accumulating sediments downslope (Boardman, 2006) and water ponding. Water ponding is often modeled through the use of infi ltration modeling techniques, such as the GreenAmpt equation (Liu et al, 2008), or it is directly observed and mapped with remote sensing techniques (Matgen et al, 2006). Models that actually predict sediment yield downslope are very rare (see the discussion in Nearing et al, 2000 andCrosson, 2000a,b).…”
Section: Introductionmentioning
confidence: 99%
“…However, these models are inaccurate when applied over wide regions and they aim at evaluating soil loss quantitatively, neglecting both the accumulating sediments downslope (Boardman, 2006) and water ponding. Water ponding is often modeled through the use of infi ltration modeling techniques, such as the GreenAmpt equation (Liu et al, 2008), or it is directly observed and mapped with remote sensing techniques (Matgen et al, 2006). Models that actually predict sediment yield downslope are very rare (see the discussion in Nearing et al, 2000 andCrosson, 2000a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of the existing studies have focused on using conceptual models and analyzing the performance of diverse topographic and wetness indices as predictive tools [e.g., Franks et al ., ; Güntner et al ., ; Grabs et al ., ; Birkel et al ., ; Ali et al ., ] and not on including surface saturation patterns in multicriterion validation [cf., Doppler et al ., ]. One reason for this is that current research still focuses on finding suitable methods to map surface saturation and its dynamics based on direct assessment according to the squishy boot method [e.g., Rinderer et al ., ], hydrometric data [e.g., Kulasova et al ., ], vegetation patterns [e.g., Kulasova et al ., ], soil morphology [e.g., Doppler et al ., ], or remote sensing data [e.g., Matgen et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the technical limitations of RS, synthetic aperture radar (SAR) is currently used (Matgen et al, 2006;Martinez & Le Toan, 2007;Rebelo et al, 2012). However, the cost and availability of SAR data cannot compete yet with optical multispectral imagery, which additionally integrates the largest time series for landscape change analysis (Frazier & Page, 2009;Qi et al, 2009;Chormanski et al, 2011;Pricope, 2012).…”
Section: Introductionmentioning
confidence: 99%